2008
DOI: 10.3324/haematol.12148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the aurora kinase inhibitors AZD1152-HQPA and ZM447439 on growth arrest and polyploidy in acute myeloid leukemia cell lines and primary blasts

Abstract: BackgroundAurora kinases play an essential role in the orchestration of chromosome separation and cytokinesis during mitosis. Small-molecule inhibition of the aurora kinases has been shown to result in inhibition of cell division, phosphorylation of histone H3 and the induction of apoptosis in a number of cell systems. These characteristics have led aurora kinase inhibitors to be considered as potential therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 26 publications
5
63
0
Order By: Relevance
“…73 In a separate study, the same group found that such CTL responses were not limited to the immunodominant WT1 [126][127][128][129][130][131][132][133][134] epitope, but could also be directed against other HLA-A*0201-restricted WT1-derived epitopes (WT1 [37][38][39][40][41][42][43][44][45] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ). 88 A similar observation was made regarding PRAME, which is known to contain at least four different HLA-A*0201-restricted epitopes that can be naturally recognized (PRA [100][101][102][103][104][105][106][107][108] , PRA 142-151 , PRA 300-309 and PRA [425][426][427][428][429]...…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 54%
“…73 In a separate study, the same group found that such CTL responses were not limited to the immunodominant WT1 [126][127][128][129][130][131][132][133][134] epitope, but could also be directed against other HLA-A*0201-restricted WT1-derived epitopes (WT1 [37][38][39][40][41][42][43][44][45] , WT1 [187][188][189][190][191][192][193][194][195] and WT1 [235][236][237][238][239][240][241][242][243] ). 88 A similar observation was made regarding PRAME, which is known to contain at least four different HLA-A*0201-restricted epitopes that can be naturally recognized (PRA [100][101][102][103][104][105][106][107][108] , PRA 142-151 , PRA 300-309 and PRA [425][426][427][428][429]...…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 54%
“…AZD1152 has been shown to significantly inhibit the growth of human colon, lung, and hematologic tumor xenografts in immunodeficient mice and as such has been selected for clinical evaluation (18,19). It has also shown tumoricidal activity against a panel of tumor cell lines including those of acute myeloid leukemia (AML) origin (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Barasertib (AZD1152) is a selective inhibitor of Aurora B kinase that can inhibit the growth of tumor cells, including those of AML origin. [11][12][13][14][15] Furthermore, barasertib has been shown to significantly inhibit the growth of human colon, lung, and hematologic tumor xenografts. 12,16 Barasertib was generally well tolerated in a phase 1 study in patients with advanced solid tumors, with neutropenia being the most frequently reported adverse event (AE).…”
Section: Introductionmentioning
confidence: 99%